Investigating and calculating the temperature of hot-spot factor for transformers - Khalid Yahya; Hani Attar; Haitham Issa; Jamal Ali Ramadan Dofan; Nassim A. Iqteit; Adel E. M. Yahya; Ahmed Amin Ahmed Solyman (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This article explores the measurement of temperature in transient states, utilizing the principles of heat transfer and thermal-electrical metaphor. The study focuses on the nonlinear thermal resistances present in various locations within a distribution transformer, while taking into account variations in oil physical variables and temperature loss. Real-time data obtained from heat run tests on a 250-MVA-ONAF cooled unit, conducted by the transformer manufacturer, is used to verify the thermal designs. The observations are then compared to the loading framework of the IEC 60076-7:2005 system. The findings of this research provide a better understanding of temperature measurement in transient states, particularly in distribution transformers, and can be applied to the design and development of more efficient and reliable transformer systems.